Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
Makes Long Mush. MAKES LONG MUSH. Miss Mary Joyce, 27-year-old Alaskan, is mushing with her dog team on a 1000-mile trek from Juneau to Fairbanks to attend the ice carnival. She went from the Taku river through Atlin, B. C; White Horse and Lake Kluane in the Yukon territory, and at last reports had hired a guide to take her through the 250-mile trackless wilderness to Tanana Crossing. She started December 20.